Examination of Grasmick et al.’s Low Self-Control Scale and of a Short Version With Cross-Gender Measurement Invariance - Pechorro, Pedro Fernandes dos Santos (Crime & delinquency, 2023)
Grasmick et al.?s Low Self-Control Scale (LSCS) is considered the gold-standard of self-control measures due to the frequency of its use in criminology. The aim of the present study is to examine the psychometric properties of the LSCS from a more modern psychometric perspective and develop a shorter version. Our sample consisted of young adults (N = 610, M = 21.33 years, SD = 3.09) from Portugal. The six-factor intercorrelated model of the LSCS showed an adequate fit, but models that would legitimate using a total score could not be confirmed. The subscales? intercorrelations revealed some low non-significant correlations. The six subscales showed distinctive correlates with other measures, with three subscales presenting some problematic correlations. Confirmatory factor analysis was subsequently used to develop a three-factor shorter version with strong cross-gender measurement invariance and good reliability. Findings have implications for the validity of the general theory of crime specifically which components of self-control have the greatest empirical linkages to conduct problems and related deviance.